Retrospective clinical evaluation of subgingival composite resin restorations with deep-margin elevation - Muscholl, Clara Caroline; Zamorska, Nadja; Schoilew, Kyrill; Sekundo, Caroline; Meller, Christian; Büsch, Christopher; Wolff, Diana; Frese, Cornelia (The journal of adhesive dentistry, 2022)
Purpose: To evaluate the long-term clinical quality of subgingivally placed composite resin restorations and the inflammatory status of surrounding supracrestal gingival and periodontal tissues. Materials and Methods: Patients with at least one subgingival restoration with deep-margin elevation placed between 2010 and 2020 at Heidelberg University Hospital and Tübingen University Hospital were identified. A sound tooth was used as control. Intraoral examination including probing depth (PD), clinical attachment level (CAL), bleeding on probing (BOP), gingival bleeding index (GBI), and plaque control record (PCR) was conducted. The clinical quality of the restorations was evaluated using the modified FDI criteria. For comparison between control and test teeth, a logistic mixed-effects model was used for GBI, PCR, and BOP, while a linear mixed-effects model was used for CAL. Multivariable linear and logistic regressions were used to examine the influence of smoking, age of restoration, number of decayed, missing and filled teeth, use of interdental brushes, and CAL. Results: Sixty-three patients were included in the study. The mean age of the restorations was 2.70 ± 1.90 years. There were no significant differences between test and control teeth with respect to inflammatory parameters BOP, GBI, and PCR. CAL was significantly higher in test teeth than in controls (p = 0.027). The regression models revealed that CAL has a significant influence on GBI (p = 0.008) and BOP (p < 0.001). A significantly increased GBI occurred especially on test teeth in patients who did not use interdental brushes daily (p = 0.010). The clinical quality of restorations was rated excellent or good in 70%, an no restoration was rated unacceptable. Conclusion: No increased inflammation was observed on sites with subgingivally placed composite restorations over an observation period of approximately 3 years. Regular interdental brush use was associated with less gingival inflammation.
Gesehen am 14.12.2022